Empyema Caused by Clostridium bifermentans: A Case Report. Issue 1 (2015) - Edagiz, Safa; Lagace-Wiens, Phil; Embil, John; Karlowsky, James; Walkty, Andrew
Abstract : A case of pneumonia with associated empyema caused by Clostridium bifermentans is described. C bifermentans is an anaerobic, spore-forming, Gram-positive bacillus. This organism is infrequently reported as a cause of infection in humans, and older publications tended to regard it as nonpathogenic. However, in more recent reports, C bifermentans has been documented as a cause of septic arthritis, osteomyelitis, soft tissue infection, abdominal infections, brain abscess, bacteremia and endocarditis. The present case is the third reported case of empyema caused by C bifermentans, and it serves to further define the spectrum of illness due to this uncommon organism.